2023
DOI: 10.37441/cejer/2023/5/2/13274
|View full text |Cite
|
Sign up to set email alerts
|

Parental Assistance with Assignments – Types of Parental Involvement in Homework

Mária-Magdolna Szász

Abstract: The present study analyses – using qualitative methods – parental involvement in children’s homework, the forms of parental involvement and the types of parents in the studied area, emphasizing the decisive role of parents in the educational life of their children, using the sample of several rural settlements in Szeklerland. By focusing on the rural context, this research contributes to the existing literature by offering a more nuanced understanding of parental involvement, potentially uncovering challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Providing homework activities to young children is common in many countries, including Tanzania. Available evidence indicates that homework plays a critical role in children's learning and acquisition of knowledge and skills in early years [3,35,47]. Homework is provided to young children to serve various purposes.…”
Section: The Concept Of Homeworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing homework activities to young children is common in many countries, including Tanzania. Available evidence indicates that homework plays a critical role in children's learning and acquisition of knowledge and skills in early years [3,35,47]. Homework is provided to young children to serve various purposes.…”
Section: The Concept Of Homeworkmentioning
confidence: 99%
“…With such participation, it is likely that parents will be able to identify and understand the child's potential and perhaps can be strengthened. Notably, higher parents' engagement in their children's homework can serve as an avenue for both collaborating and achieving intended learning outcomes, which in turn improve academic performance [1,3,18,22,34,47]. Other researchers have also reported that parents' involvement in homework can foster children's autonomy, good habits and emotional encouragement to struggling learners [5,26,55].…”
Section: Perceived Learning Opportunities In Supporting Children With...mentioning
confidence: 99%
See 1 more Smart Citation